Morphometric Analysis of the Corpus Callosum According to Age and Sex in Middle Eastern Arabs: Racial Comparisons and Clinical Correlations to Autism Spectrum Disorder - Allouh, Mohammed Z.; Al Barbarawi, Mohammed M.; Ali, Heba A.; Mustafa, Ayman G.; Alomari, Safwan O. (Frontiers in Systems Neuroscience, 2020)
This study sought to examine the influence of age and sex on morphometric measurements of the corpus callosum (CC) within Middle Eastern Arab population, in order to obtain reference data and conduct racial comparisons with previously reported measurements from other ethnicities. Furthermore, it aimed to investigate CC variations that may occur in children with autism. To this end, magnetic resonance images of normal brains were acquired from three different age groups, consisting of children, younger adults, and older adults. Brain images were also acquired from boys with autism spectrum disorder (ASD). The CC length, area, and thickness were measured. The CC length was smaller in children than in the other age groups, but no difference in CC length was found between younger and older adults. The CC area and thickness were greater in younger adults than in children and older adults, and greater in older adults than in children. With regard to sexual dimorphism, the CC area and forebrain volume were larger in male children than in female children. No sex-related differences in CC area or thickness were found in adults. However, the ratio of CC area to the forebrain volume was greater in adult females than in males, owing to the smaller forebrain volume in females. The absolute length of the CC was greater in older adult males than in their female counterparts. In addition, significant differences in CC measurements were found in comparison to measurements obtained from other ethnicities. Lastly, significant reductions in CC area and thickness were found in boys with ASD compared to their neurotypical peers. In conclusion, age and sex significantly influence morphometric measurements of CC in Middle Eastern Arab population. This study points to the presence of racial differences in CC size. Finally, it reveals that children with ASD display a distinct reduction in CC size compared to neurotypical children of the same ethnicity.